Profitability and Leverage on Tax Avoidance: The Moderating Role of Firm Size in Indonesian SOEs - Mariawati Mariawati; Meythi Meythi; Riki Martusa; Filia Theresia Kurniawaty (Owner : Riset dan Jurnal Akuntansi, 2026)
This study examines the effect of profitability and leverage on tax avoidance with firm size as a moderating variable in Indonesian state-owned enterprises (SOEs) during 2020–2024. This study uses secondary data obtained from annual financial reports of SOEs listed on the Indonesia Stock Exchange and applies panel data regression analysis. The sample was selected using purposive sampling. The Chow, Hausman, and Lagrange multiplier tests are used to pick models, and the Fixed Effects Model is determined to be the best estimating technique. Given that its impact on the Effective Tax Rate (ETR) is statistically significant and positive, the results of the empirical research demonstrate that greater profitability (ROA) is associated with higher ETR, indicating lower levels of tax avoidance. Conversely, the DER suggests that leverage has no significant effect on tax avoidance. Additionally, it has been noted that firm size (FS) has a moderating effect on the profitability tax avoidance nexus, weakening the positive effect of profitability on ETR. Nevertheless, the relationship between leverage and tax avoidance is not moderated by the FS. The study focuses on the significance of firm-specific characteristics and contributes actual data on tax avoidance practices to the literature on accounting and taxation in SOEs. Practically speaking, the results can help legislators and tax authorities create more efficient government surveillance programs to increase tax payments, particularly among the biggest and most lucrative SOEs.